Global metabolic profiling for the study of Rhizoma Paridis saponins‐induced hepatotoxicity in rats. Issue 1 (21st November 2015) - Man, Shuli; Qiu, Peiyu; Li, Jing; Zhang, Liming; Gao, Wenyuan
ABSTRACT: Rhizoma Paridis saponins (RPS) is a traditional Chinese medicine (TCM) from the plant Paris polyphylla var. yunnanensis (Fr.) Hand.‐Mazz. Despite its potentially clinical utility such as anticancer and anti‐inflammation, it has slight side effects and toxicity as previous report. In this work, 90‐day administration of RPS induced liver injury. 1 H‐NMR‐ and GC/MS‐based metabonomic analyses in conjunction with histopathological examinations, blood biochemistry and hepatic phase I and II enzymes assays were performed to evaluate the toxic mechanisms of RPS induced in rats. As a result, oral administration of RPS possessed certain liver toxicity in SD rats. 1 H‐NMR and GC/MS data indicated that RPS inhibited the oxidation of fatty acids, glycolysis, and TCA cycle pathway, and disturbed glycine, serine, and threonine metabolism. Low expression of TG, T‐CHO, and LDL‐C and high levels of ALT and AST indicated that chronic exposure to RPS caused hepatocyte damage, synthesis dysfunction, and transportation failure of lipoproteins. In addition, RPS downregulated the mRNA levels of CYP1A2, CYP2E1, and UGTs. In conclusion, we used metabonomics approach to study the toxicity of RPS for the first time. This research demonstrated that metabonomics method was a promising tool to study and diagnose TCM‐induced toxicity. © 2015 Wiley Periodicals, Inc. Environ Toxicol 32: 99–108, 2017.